Complete chloroplast genome of the hot desert herb Fagonia indica (Zygophyllaceae) from south-central Arabia. Issue 2 (3rd July 2019) - Ali, Mohammad Ajmal; Elshikh, Mohammad S.; Kim, Soo-Yong; Al-Hemaid, Fahad; Lee, Joongku; Lama, Dorjay; Chhetri, Abhijit; Pan, Tapan Kumar
Abstract: The complete chloroplast genome sequences of the hot desert herb Fagonia indica (Zygophyllaceae) is being reported in this study. The total plastome length was 128, 379 bp (GC content 34.02%). The gene order in F. indica was found similar to the angiosperm except for the loss of one copy of the IR and by the presence of a single, large inversion that reverses the order of the genes between rbcL and rps16. A total number of 115 unique coding genes which includes 80 protein-coding gene, 31 tRNA genes, and 4 rRNA genes were annotated. The phylogenetic analysis of representative plastomes from the Roisds revealed two distinct clades of Krameriaceae and Zygophyllaceae.